Is economics a man's business? Exploring the long-term effects of the gender gap in economic competencies at the upper secondary level on students' choice to study economics at university. (December 2019) - Jüttler, Michael; Schumann, Stephan
In higher education, across countries, a large share of students choose to study economics. Although there is only a small difference in the share of female and male students in that field, there is robust empirical evidence of a gender gap in economic competencies, showing that male students in most cases outperform female students. There is a broad discussion about the differences in gender-specific socializations that cause this gender gap. However, no research exists on the long-term effects of this gender gap. This study uses longitudinal and representative data of N = 1397 Swiss students (824 female students) to analyse the gender-specific effects of economic competencies at the end of the upper secondary level on their aspiration and decision to study economics. The results show that economic knowledge and interest in economics have a substantially stronger effect on the choice of economics for female students. The aspiration to study strongly mediates these effects. We argue that these results can mainly be traced back to different interests and self-perceptions of skills and abilities in economics caused by gender-specific socialization. Possible implications of gender socialization and discrimination in economics for secondary and higher education and for the labour market are discussed.